Effects of mindfulness-based interventions on cognition in people with multiple sclerosis: a systematic review and meta-analysis of randomized controlled trials - Komar, Alyssa; Dickson, Kirsty; Alavinia, Mohammad; Bruno, Tania; Bayley, Mark; Feinstein, Anthony; Scandiffio, Jillian; Simpson, Robert (Frontiers in Psychiatry, 2024)
Introduction Cognitive impairment affects up to 65% of people with multiple sclerosis (PwMS), undermining functional independence and quality of life. The objective of this study is to synthesize existing randomized controlled trial (RCT) evidence on the effects of Mindfulness-based interventions (MBIs) on cognitive function in PwMS. Methods A systematic literature search was conducted to identify RCTs assessing MBIs effects on cognitive functioning in PwMS. Using pre-defined criteria, two independent reviewers screened titles, abstracts, and extracted data from included studies. Meta-analysis was performed, where possible, using a random effects model. Narrative synthesis was undertaken. Preferred Reporting Items for Systematic Reviews and Meta-analysis guidance was followed. PROSPERO_ID:(CRD42021286429). Results Twelve eligible RCTs were identified, n=700 PwMS. MBIs included both standardized and tailored interventions, in-person and virtually. A variety of measures of cognitive functioning were reported. Five studies (n=254 PwMS) were included in meta-analysis; pooled results suggested MBIs effectively improved scores on the Paced Auditory Serial Addition Test (PASAT)-2 (SMD=0.38; 95% CI 0.06-0.71; I2 63%; p=0.02), whereas improvements were of borderline significance on the PASAT-3 (SMD=0.32; 95% CI -0.01-0.64; I2 65%; p=0.06), and, although trending to positive, were statistically insignificant on the Perceived Deficits Questionnaire (SMD=0.34; 95 CI -0.05-0.74; I2 0%; p=0.09) and Symbol Digits Modality Test (SMD=0.25; 95% CI -0.15-0.66; I2 0%; p=0.21). Conclusion Preliminary findings in meta-analysis are inconsistent but suggest potential benefits from MBI training on cognitive functioning in PwMS. High quality RCTs are necessary to test more definitively the impact of MBIs on cognitive functioning in PwMS. Systematic review registration PROSPERO, identifier CRD42021286429.